The Growth of Skeletonema costatum on Various Salinity Level’s Media - Siti Rudiyanti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
ABSTRACT Skeletonema costatum is a good species phytoplankton for natural food since it has high chemical contents. The research aims to know salinity influence to the growth of S costatum’s and its optimum salinity. Experimental method is used with 4 treatments and 1 control. The primary research done to identify observation time and accurate interval salinity. Result of the primary research showed that S costatum’s growth can be observed clearly in every 18 hours and salinity level with interval of 3 0/00. The salinity treatments used 230/oo, 260/oo, 290/oo, 320/oo, and 350/oo because of it’s salinity range of S costatum. Cell density in each bottle sample is 20.000 cell/liter. The maximal population growth of S costatum at salinity 23 0/00 is 2,5 x 104 cell /mL, salinity 26 0/00 is 2,58 x 104 cell/mL, salinity 29 0/00 is 3,03 x 104cell/m, and at control salinity 32 0/00 is 4,08 x 104 cell/mL, while at salinity 35 0/00 is 3,16 x 104 cell/mL. From the observation found that water quality of media is suitable to support population growth of S costatum. The best salinity for the growth of S costatum population is on the treatment of 32 0/00 salinity where the cell grown very fast and only need short time to reach out the top population. Whereas the optimum salinity is 33,26 0/00 on density of 3,48 x 104 cell/mL. Keywords : Skeletonema costatum, growth, optimum salinity.